(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Studies were carried out to produce potential biodiesel from non-edible oil of Jatropha curcus. Due to its high free fatty acid (12% FFA), the crude Jatropha oil was processed in two steps: the acid-catalyzed esterification and followed by the base-catalyzed transesterification. The first step reduced the FFA level to less than 1% in 1h at 50°C for the 0.40 w/w methanol-to-oil ratio with 1% w/w of H2SO4. After the reaction, the mixture was stagnated for an hour and the methanol-water upper layer was discarded. The second step converted the product of the first step into biodiesel and glycerol through transesterification using 0.20 w/w methanol-to-oil and 0.5% w/w NaOH to oil as alkaline catalyst at 65°C. The maximum yield of biodiesel (organic phase of upper layer) and fatty acid methyl esters (FAME) yield were achieved at about 95% and 84% within 1 hour respectively. The glycerol concentration in the byproduct (glycerol layer) obtained after dual step transesterification was found 32%. Key words: Jatropha curcus, Biodiesel, Esterification, Glycerol and Fatty acid DOI: 10.3329/bjsir.v44i3.4409 Bangladesh J. Sci. Ind. Res. 44(3), 347-352, 2009